2021
DOI: 10.1136/bmjopen-2021-051173
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for group arts therapies: a cross-sectional survey of mental health patients and the general population

Abstract: ObjectivesThe arts therapies include music therapy, dance movement therapy, art therapy and dramatherapy. Preferences for art forms may play an important role in engagement with treatment. This survey was an initial exploration of who is interested in group arts therapies, what they would choose and why.DesignAn online cross-sectional survey of demographics, interest in and preferences for the arts therapies was designed in collaboration with patients. The survey took 10 min to complete, including informed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Offering a safe and structured opportunity to access and express these feelings can lead to cathartic expression and a sense of experiential relief. From Supporting the views of over 60% of the participants in the survey of service users and members of the public who value creative methods in psychotherapy (Millard et al, 2021), the service users participating in this study also championed the need for creative psychotherapies in the NHS. It could be argued that the group of service users in this study, as a self-selected convenience sample that were already attendees of an arts and crafts group, could skew the findings presented here.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Offering a safe and structured opportunity to access and express these feelings can lead to cathartic expression and a sense of experiential relief. From Supporting the views of over 60% of the participants in the survey of service users and members of the public who value creative methods in psychotherapy (Millard et al, 2021), the service users participating in this study also championed the need for creative psychotherapies in the NHS. It could be argued that the group of service users in this study, as a self-selected convenience sample that were already attendees of an arts and crafts group, could skew the findings presented here.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that the combination of art forms within sessions can meet different preferences for art media, as reported by service users and the general public in recent studies (Millard et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The charity MIND identified arts-based approaches as one of their clients’ top preferences for psychological support [ 12 ], whilst clients in deprived areas also reported their preference for more creative interventions [ 13 ]. More recently, a survey completed by Millard et al [ 14 ] that included 1541 participants (685 mental health patients and 856 members of the general population) showed that 60% were very interested in group arts therapies. However, non-verbal, creative, arts-based interventions such as therapies are rarely used in the North West of England in statutory services.…”
Section: Introductionmentioning
confidence: 99%